Republic of Madagascar : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2015)
KEY ISSUES Context: Madagascar is one of the poorest countries in the world. Weak economic growth has contributed to persistent and increasing poverty with deteriorating social indicators. In a fragile environment, the uncertainty linked to political instability, weak institutions, and weak governance has eroded the foundation for solid economic growth, with short-term rent-seeking having taken precedence over longer-term nation building. Outlook and Risks: The authorities are at a crossroads. A well-prioritized medium-term economic program that is implemented concertedly would increase growth and reduce poverty. This will require resources in order to undertake essential investment in infrastructure, as well as to increase social spending on education and health. However, there are downside risks, whereby a slow pace of reform implementation would keep Madagascar on a path of economic stagnation and persistent poverty. Fiscal Policy: There is a need to increase fiscal space in order to raise the level and efficiency of pro-poor/pro-growth spending while preserving debt sustainability. This will involve a broadening of the tax base, supported by a comprehensive revenue mobilization strategy, improving the composition and quality of budgetary spending, and reinforcing public financial management. Monetary and Exchange Rate Policies: To facilitate an active monetary policy and safeguard macroeconomic stability, it will be important to increase central bank independence, strengthen its oversight mechanisms, and recapitalize the central bank. A floating regime remains appropriate, but it will be important to ensure that the foreign exchange market is liquid and reflects market conditions. Structural Reforms: There is a need to strengthen the economic climate, including through improved governance and social development policies that would send a clear signal, both within society and to development partners, confirming the government's commitment to reform. To help build public support for continued reforms, it would be advisable to build an early track record of 'small victories/quick wins'.